CAT score single item analysis in patients with COPD: Results from COSYCONET - Siemens, Sarah Marietta von; Kauczor, Hans-Ulrich; Jobst, Bertram; Gogol, Manfred; Herth, Felix; Katus, Hugo (Respiratory medicine, 2019)
The COPD Assessment Test (CAT) is in widespread use for the evaluation of patients with chronic obstructive pulmonary disease (COPD). We assessed whether the CAT items carry additional information beyond the sum score regarding COPD characteristics including emphysema. Patients of GOLD grades 1 to 4 from the COPD cohort COSYCONET (German COPD and Systemic Consequences - Comorbidities Network) with complete CAT data were included (n=2270), of whom 493 had chest CT evaluated for the presence of emphysema. Comorbidities and lung function were assessed following standardised procedures. Cross-sectional data analysis was based on multiple regression analysis of the single CAT items against a panel of comorbidities, lung function, or CT characteristics (qualitative score, 15th percentile of mean lung density), with age, BMI and gender as covariates. This was supported by exploratory factor analysis. Regarding the relationship to comorbidities and emphysema, there were marked differences between CAT items, especially items 1 and 2 versus 3 to 8. This grouping was basically confirmed by factor analysis. Items 4 and 5, and to a lower degree 1, 2 and 6, appeared to be informative regarding the presence of emphysema, whereas the total score was not or less informative. Regarding comorbidities, similar findings as for the total CAT score were obtained for the modified Medical Research Council scale (mMRC) which was also informative regarding emphysema. Our findings suggest that the usefulness of the CAT can be increased if evaluated on the basis of single items which may be indicating the presence of comorbidities and emphysema.